The Casa Río Laboratory and its La Plata Voices Archive - Fabres, Paola (Farol, 2025)
This article analyzes the relationship between art and territory through the work Living Rivers, presented in the exhibition The Earth Will Not Abide (Gallery 400, Chicago, 2017). The study shows how situated artistic practices can make visible socio-environmental conflicts in the Mississippi and La Plata river basins, territories impacted by agribusiness and transnational extractivist dynamics. It argues that Living Rivers, by mobilizing collaborative cartographies and local narratives, operates as a critical device for territorial interpretation. The article also discusses the project’s unfolding in the Casa Río Lab Archive, which consolidates a repertoire of community memory and resistance.